The Influence of Social Media Marketing, Brand Image, and Word of Mouth on Purchasing Decisions of Arak Bali Beverages in Bali Province - Thompson, I Wayan Bima; Bagus Aristayudha, A. A. Ngurah; Surya Astitiani, Ni Luh Putu (West Science Interdisciplinary Studies, 2024)
As a regional staple that is of considerable cultural and economic significance in the Bali region, Arak Bali is the subject of this study, which aims to investigate the influence that social media marketing, brand image, and word of mouth have on the decisions that customers make about the purchase of Arak Bali. In a preliminary study with 10 participants, it was discovered that twenty percent of respondents were more interested in purchasing Arak Bali, while eighty percent preferred alcoholic beverages that were imported from other countries. This was the finding of the survey. For the purpose of this investigation, a quantitative methodology is applied, with a specific emphasis placed on the positivist paradigm. In addition to that, a survey that is comprised of questionnaires and random sampling is utilized. This study is centered on individuals who are wine drinkers and who reside in the province of Bali. These individuals are the focus of the investigation. For the purpose of this experiment, the sampling was carried out using the method of random sampling, and samples were gathered from as many as one hundred different individuals. Subsequent to the implementation of a double linear regression analysis strategy, the data is processed with the help of SPSS software version 29, which is the method that is utilized for the purpose of data analysis. The conclusions of this study indicate that the significance value of social media marketing is 0.001 less than 0.05, the significance value of brand image is 0.007 less than 0.05, and the meaning value of word of mouth is 0.001 less than 0.05. As a result, it is possible to draw the conclusion, on the basis of the analysis of the data, that social media marketing, brand image, and word of mouth have a substantial positive influence on the decision to purchase Bali Beverages in the province of Bali. Based on the data, it can be concluded that good marketing through social media, the building of a powerful brand image, and positive word of mouth all have a significant impact on the decisions that consumers make regarding their purchases. These findings provide essential information that can be utilized by Arak Bali in the development of its marketing strategy in highly competitive sectors.